Trans-nasal-trans-sphenoidal brain injury by a fencing foil: an unusual case report and brief literature review - Özay, R.; Balkan, M. S.; Tönge, Ç.; Sekerci, Z. (The Journal of Sports Medicine and Physical Fitness, 2017)
In this report, the authors present an unusual case of a 10-year-old child who suffered a severe headache and rhinorrhea that occurred as a result of fencing foil sports injury via trans-nasal-trans-sphenoidal (TNTS) pathway. Following trauma, the child had shown neurological symptoms such a pupil dilatation, change in consciousness and mild hemiparesia. Imaging demonstrated destruction of bone structures including posterior wall of sphenoid sinus and antero-superior part of sella turcica, and also a contusion at right thalamic region. For treatment of rhinorrhea lumbar drainage system (LDS) had planted in order to relieve cerebrospinal fluid (CSF) leakage. After the treatment, the patient had fully recovered without any need of further surgical intervention. CSF leakage had prevented and neurological symptoms were completely treated. This case represents the first report of brain injury via TNTS pathway in a sports practice. Diagnosis, clinic follow-up and treatment options of this rare accidental sports injury are discussed.